Workshop Program Kreativitas Mahasiswa Sebagai Penguatan Gerakan Gemar Menulis Ilmiah - Any Fatmawati; Ika Nurani Dewi; Akhmad Sukri; Septiana Dwi Utami; Muhammad Arief Rizka; Saipudin Sapina (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
The purpose of this service activity is to increase the knowledge and competence of Undikma Biology Education study program students in preparing PKM (Student Creativity Program) 2023 proposals as an effort to strengthen the scientific writing movement. The method of implementing this service is a workshop which is conducted online via zoom. Participants in this activity were 122 students and lecturers of Biology education. The evaluation instrument is in the form of a response questionnaire from activity participants. Data analysis technique uses a Likert scale. Indicators of the success of the activity can be seen from the enthusiasm of the participants who took part in the activity from other study programs and some even came from outside the region, there were interactive discussions between participants and presenters, and the formation of 16 PKM groups with various fields of study. The results of this service activity show that 92% of the participants responded to this activity that their knowledge and competence related to PKM increase.